(untitled) (Essen, 2014)
Deals with aluminium as material and its recovery from bauxite, the various process steps and procedures, melting and casting plants, metal treatment facilities, provisions and equipment for environmental control and workforce safety, cold and hot recycling of aluminium including scrap preparation and remelting, operation and plant management
Keywords: Nhôm,Nhôm,Aluminum,Aluminum; Tái chế,Luyện kim,Recycling,Metallurgy